The Effect of Autoclave Sterilization on the Fracture Resistance of ProTaper Rotary Files - N Roghanizad; Z Khalilak; M Vatanpour; S Haghi; P Alirezayi; Z Movassagh (Islamic Azad University, 2016)
Background and aim: The purpose of this study was to evaluate the effect of autoclave sterilization on the fracture rate of ProTaper instruments (ex vivo). Materials and methods: One hundred shaping and finishing ProTaper instruments were used in a crown - down technique for cleaning and shaping the mesial canals of extracted mandibular molars using 5.25% NaOCl for irrigation. In the experimental group, 50 files were steam autoclaved before each use. In the control group, the files were not exposed to the sterilization process. The working time was reported for each file. Independent t- test was employed to evaluate the statistical significance of the measured values. Results: The instruments that underwent the sterilization processes did not show any statistically significant differences in comparison with those of the control group. Conclusions: The results of this study showed that sterilization in autoclave in the presence of NaOCl did not lead to a decrease in survival time of the files.